2010
DOI: 10.1113/jphysiol.2009.178137
|View full text |Cite
|
Sign up to set email alerts
|

The mechanism of the resistance to stretch of isometrically contracting single muscle fibres

Abstract: Rapid attachment to actin of the detached motor domain of myosin dimers with one motor domain already attached has been hypothesized to explain the stretch-induced changes in X-ray interference and stiffness of active muscle. Here, using half-sarcomere mechanics in single frog muscle fibres (2.15 μm sarcomere length and 4• C), we show that: (1) an increase in stiffness of the half-sarcomere under stretch is specific to isometric contraction and does not occur in rigor, indicating that the mechanism of stiffnes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
54
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(61 citation statements)
references
References 65 publications
7
54
0
Order By: Relevance
“…22), increasing P c more significantly than what is observed at low Ca 2ϩ concentrations. The force produced during stretch after blebbistatin treatment increases such that it virtually overlaps with the force produced before blebbistatin.…”
Section: Discussionmentioning
confidence: 65%
“…22), increasing P c more significantly than what is observed at low Ca 2ϩ concentrations. The force produced during stretch after blebbistatin treatment increases such that it virtually overlaps with the force produced before blebbistatin.…”
Section: Discussionmentioning
confidence: 65%
“…48 In conclusion, for an identical level of EMG activity, the in vivo behavior of GM and TA muscle assessed via its architecture was different during either isometric agonist or antagonist contractions. As suggested by the interplay between stretching of the series elastic component (SEC) and the isometric contraction at the molecular level, 49 our findings further highlight the complexity of the isometric contraction. At the fascicle level, we have found that the tension produced during this mode of contraction is not strictly achieved isometrically, whether the muscle behaves as an agonist or an antagonist.…”
Section: Methodologicalmentioning
confidence: 74%
“…Some authors suggest that the increase in force is caused by an increased mean force produced by the cross-bridges [50,51] and a redistribution of cross-bridges between pre-powerstroke and post-powerstroke states [19,22,23,26,52]. Others suggest the increase in force is caused by an increase in the number of cross-bridges attached to actin [49,53], which may include the involvement of a second, adjacent cross-bridge that shares the same myosin neck fragment. Regardless of the actual mechanism, the increase in stiffness vanishes quickly after stretch, to levels between 0 and 7 per cent (between 10 and 300 ms after the stretch) [19,49], which weakens the possibility that cross-bridges contribute to the residual force enhancement.…”
Section: Mechanisms Of Force Enhancementmentioning
confidence: 99%